Mechanosensitive TRPC1 channels promote calpain proteolysis of talin to regulate spinal axon outgrowth. (2013)
Intracellular Ca(2+) signals control the development and regeneration of spinal axons downstream of chemical guidance cues, but little is known about the roles of mechanical cues in axon guidance. Here we show that transient receptor potential canonical 1 (TRPC1) subunits assemble mechanosensitive (MS) channels on Xenopus neuronal growth cones that regulate the extension and direction of axon outgrowth on rigid, but not compliant, substrata. Reducing expression of TRPC1 by antisense morpholinos inhibits the effects of MS channel blockers on axon outgrowth and local Ca(2+) transients. Ca(2+) influx through MS TRPC1 activates the protease calpain, which cleaves the integrin adaptor protein talin to reduce Src-dependent axon outgrowth, likely through altered adhesion turnover. We found that talin accumulates at the tips of dynamic filopodia, which is lost upon cleavage of talin by active calpain. This pathway may also be important in axon guidance decisions since asymmetric inhibition of MS TRPC1 is sufficient to induce growth cone turning. Together our results suggest that Ca(2+) influx through MS TRPC1 on filopodia activates calpain to control growth cone turning during development.